2008
DOI: 10.1644/07-mamm-a-192.1
|View full text |Cite
|
Sign up to set email alerts
|

Prey Selection by Marine-Coastal River Otters (Lontra canadensis) in Newfoundland, Canada

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…However, several other dietary studies have also found a large number of bullheads in otter diet (see Copp and Roche 2003), with some noting preferential selection (Almeida et al 2012). Cote et al (2008) also found a preference for slow-swimming marine cottids in North American river otters. In contrast, Britton et al (2006) reported bullheads and cyprinids to be of equal importance and present in otter diet in similar amounts throughout the year.…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 94%
“…However, several other dietary studies have also found a large number of bullheads in otter diet (see Copp and Roche 2003), with some noting preferential selection (Almeida et al 2012). Cote et al (2008) also found a preference for slow-swimming marine cottids in North American river otters. In contrast, Britton et al (2006) reported bullheads and cyprinids to be of equal importance and present in otter diet in similar amounts throughout the year.…”
Section: Evidence For Prey Selection By Ottersmentioning
confidence: 94%
“…Therefore, if the diet of otters fails to fluctuate according to prey availability, then it is likely that they are selectively foraging. Otter diet does, however, often tend toward seasonal fluctuation (although not always; see Cote et al 2008), most notably in relative proportions of fish and crayfish from summer to winter (Tumlison and Karnes 1987;Miller 1992;Noordhuis 2002;Roberts et al 2008). At a finer taxonomic scale, seasonal differences in occurrence of fish families in otter diet are also common (Greer 1955;Sheldon and Toll 1964;Anderson and Woolf 1987;McDonald 1989;Reid et al 1994;Cogliano 2003;Roberts 2003;Roberts et al 2008;Wengeler et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…While otters consume a large number of species, they feed mostly on fish and shellfish (90% of their diet), and less so on other invertebrates, amphibians, birds, and mammals (Anderson‐Bledsoe and Scanlon ; Carss ; Cote et al ; Evans et al ; Fretueg et al ; Kean et al ; Mason et al ; Reid et al ). This is of prominent conservation concern because the position of river otters at the top of the food chain increases their susceptibility to bioaccumulation of a wide‐range of contaminants (Anderson‐Bledsoe and Scanlon ; Evans et al ; Kean et al ; Mason et al ).…”
Section: Exposure To Anthropogenic Pollutantsmentioning
confidence: 99%